Analysis of geothermal temperatures for heat pumps application in Paraná (Brasil) - Santos, Alexandre F. (2016)
Geothermal heat pumps are broadly used in developed countries but scarcely in Brazil, in part because there is a lack of Brazilian soil temperature data. The aims of this work are: to present soil temperature measurements and to compare geothermal heat pump system performances with conventional air conditioning systems. Geothermal temperature measurement results are shown for ten Paraná State cities, representing different soil and climate conditions. The measurements were made yearlong with calibrated equipment and digital data acquisition system in di erent measuring stations. Geothermal and ambient temperature data were used for simulations of the coe cient of performance (COP), by means of a working uid pressure-enthalpy diagram based software for vapor-compression cycle. It was veri ed that geothermal temperature measured between January 13 to October 13, 2013, varied from 16 to 24 °C, while room temperature has varied between 2 and 35 °C. Average COP values for conventional system were 3.7 (cooling mode) and 5.0 kW/kW (heating mode), corresponding to 5.9 and 7.9 kW/kW for geothermal system. Hence it was verified an average efficiency gain of 59%with geothermal system utilization in comparison with conventional system.